Upaya Peningkatan Kemampuan Pemahaman Matematis dan Kerja Sama Siswa Pada Mata Pelajaran Matematika Materi Pecahan Melalui Pendekatan Matematika Realistik Indonesia Di Kelas V SDN 3 Medayu - Shifa Salsabila; Muryaningsih, Sri (Jurnal Gentala Pendidikan Dasar, 2025)
This study aims to examine the improvement of mathematical understanding and collaboration skills among fifth-grade students at SDN 3 Medayu through the application of the Indonesian Realistic Mathematics Education (PMRI) approach in leaming fractions. The research employed a Classroom Action Research (CAR) design conducted over two cycles, each comprising two sessions. The study was deemed successful if it met the following indicators: at least 75% of students achieved the Minimum Mastery Criterion (KKTP) with a score of 75 or higher, and there was a measurable improvement in students collaboration skills from Cycle I to Cycle II, reaching a "good" category. The results indicated a significant increase in students' mathematical understanding. In Cycle I, the average student score was 72.8 with a mastery rate of 64.42%. This improved in Cycle II, where the average score rose to 83.98 and the mastery rate increased to 85.43%. In addition, students' cooperative attitude also showed improvement, as evidenced by the results of observations and questionnaires. In Cycle I, the average observation score was 2.26, which falls into the ‘adequate’ category, and the questionnaire showed an average score of 3,10. In Cycle II, the average observation score increased to 3.05, which falls into the ‘good’ category, and the average questionnaire score rose to 3,27. These findings suggest that implementing the PMRI approach in teaching fractions effectively enhances both mathematical understanding and collaboration skills among fifth-grade students at SDN 3 Medayu.